2020
DOI: 10.1016/j.stem.2020.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule PAPD5 Inhibitors Restore Telomerase Activity in Patient Stem Cells

Abstract: Highlights d High-throughput screening identifies specific small-molecule PAPD5 inhibitor BCH001 d BCH001 restores telomere length in iPSCs from patients with dyskeratosis congenita d Repurposed HBsAg suppressors, dihydroquinolizinones, increase TERC in stem cells d Oral PAPD5 inhibitors restore TERC and telomeres in human HSPCs in vivo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
68
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 91 publications
3
68
1
1
Order By: Relevance
“…RG7834 treatment was sufficient to restore the in vitro definitive hematopoietic development of DKC1_A353V hESCs, similarly to what we have recently observed with the genetic silencing of PAPD5. 18 Although these experiments represent the first nongenetic rescue of hematopoietic development from hESCs in DKC1 mutant cells, it has recently been shown that PAPD5 inhibitors are able to promote telomere restoration in different patient-derived DC samples in vitro and in vivo, through xenotransplantation assays 27 ;…”
Section: Resultsmentioning
confidence: 99%
“…RG7834 treatment was sufficient to restore the in vitro definitive hematopoietic development of DKC1_A353V hESCs, similarly to what we have recently observed with the genetic silencing of PAPD5. 18 Although these experiments represent the first nongenetic rescue of hematopoietic development from hESCs in DKC1 mutant cells, it has recently been shown that PAPD5 inhibitors are able to promote telomere restoration in different patient-derived DC samples in vitro and in vivo, through xenotransplantation assays 27 ;…”
Section: Resultsmentioning
confidence: 99%
“…104 In terms of tolerability, PAPD5 null human cell lines and pluripotent stem cells are able to be isolated and propagated indefinitely, and show decreased TERC oligo-adenylation and increased TERC levels. 102,114 These observations provide the basis for considering PAPD5 a "druggable" target to restore TERC and telomere length in certain forms of DC/TBDs 100 ( Figure 2B).…”
Section: Therapeutic Potential Of Modulating Terc Processingmentioning
confidence: 95%
“…As described above, several studies have demonstrated that genetic inhibition of PAPD5 can restore TERC levels in PARN-or dyskerin-deficient states. 96,[98][99][100]102,104,114 Stable long-term shRNA-mediated PAPD5 depletion is tolerated in PARN-mutant patient iPSCs and restores TERC levels, telomerase activity and telomere length 100 ( Figure 2B).…”
Section: Therapeutic Potential Of Modulating Terc Processingmentioning
confidence: 99%
See 2 more Smart Citations